Alterations of the Motor and Olfactory Functions Related to Parkinson’s Disease in Transgenic Mice With a VMAT2-Deficiency in Dopaminergic Neurons - Jiang, Song; Berger, Stefan; Hu, Yajuan; Bartsch, Dusan; Tian, Yanghua (Frontiers in Neuroscience, 2020)
Parkinson’s disease (PD) is one of the most common neurodegenerative diseases, with approximately 6 million people affected worldwide. Vesicular monoamine transporter 2 (VMAT2) dysfunction has recently become a hot topic in the pathophysiology of PD, and the advent of transgenic mice has also accelerated the development of behavioral studies in animal models. However, there are only a few systematic behavioral tests that embrace abundant motor and nonmotor performance in a unique mutant mouse model that corresponds to the varied symptoms observed in human PD. The aim of this study is to evaluate the responsibility of the unique reduction of dopamine in the varied motor and nonmotor symptoms of PD via transgenic mice model. We analyzed neurotransmitter concentrations in the brain tissue of 18-month-old mutant mice with selective inactivation of one allele of Vmat2 in dopaminergic neurons (VMAT2DATcre-HET) to confirm the selective reduction of dopamine, and then examined behavioral functions. Neurochemical tests showed lower dopamine concentrations in specific brain regions of VMAT2DATcre-HET mice, especially the ventral tegmental area/substantia nigra and striatum, together with relatively unchanging concentrations of norepinephrine and serotonin, demonstrating the dopaminergic specificity of this mouse model. Behavioral tasks showed impairments in several motor functions and major defects in olfactory abilities in the VMAT2DATcre-HET mice; however, no significant changes were found in the majority of nonmotor tests, such as emotional performance and sleep patterns. We concluded from this study that the selective inactivation of one allele of the Vmat2 gene in dopaminergic neurons was related to dopamine reduction, resulting in phenotypes resembling some of the major deficits in PD, especially motor symptoms and olfactory function.